2015
DOI: 10.1021/jacs.5b08752
|View full text |Cite
|
Sign up to set email alerts
|

Facile Conversion of Hydroxy Double Salts to Metal–Organic Frameworks Using Metal Oxide Particles and Atomic Layer Deposition Thin-Film Templates

Abstract: Rapid room-temperature synthesis of metal-organic frameworks (MOFs) is highly desired for industrial implementation and commercialization. Here we find that a (Zn,Cu) hydroxy double salt (HDS) intermediate formed in situ from ZnO particles or thin films enables rapid growth (<1 min) of HKUST-1 (Cu3(BTC)2) at room temperature. The space-time-yield reaches >3 × 10(4) kg·m(-3)·d(-1), at least 1 order of magnitude greater than any prior report. The high anion exchange rate of (Zn,Cu) hydroxy nitrate HDS drives the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
140
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 179 publications
(151 citation statements)
references
References 33 publications
7
140
0
Order By: Relevance
“…most likely because of dehydration and rehydration. 41 In addition, broader XRD peaks are observed in the patterns of CuBTC_An than those in the patterns of C-Cu-BTC and the simulation result, which can be attributed to either the small crystallite size or abundance of lattice defects. 42,43 These crystal structures were further studied using FTIR spectroscopy.…”
Section: Calculationsmentioning
confidence: 70%
“…most likely because of dehydration and rehydration. 41 In addition, broader XRD peaks are observed in the patterns of CuBTC_An than those in the patterns of C-Cu-BTC and the simulation result, which can be attributed to either the small crystallite size or abundance of lattice defects. 42,43 These crystal structures were further studied using FTIR spectroscopy.…”
Section: Calculationsmentioning
confidence: 70%
“…These two peaks are associated with vibrations of the NO3 groups mainly present in the (Zn, Cu) hydroxy nitrate double salt. 33 The integrated peak area for vfalse(NO3false) at ≈ 1420 cm −1 (Figure 2b) increases dramatically and reaches saturation after 1 min, indicating the fast formation of (Zn,Cu) HDS from the ZnO thin film. Following the exposure of the ZnO surface to Cu(NO 3 ) 2 solution, ethanol-water solvent mixture was used to rinse the cell for 1 min.…”
Section: Resultsmentioning
confidence: 98%
“…Sets of spectra were analyzed by integrating the peaks for vfalse(NO3false) at ≈ 1420 cm −1 , v (C=C) at ≈ 1588 cm −1 and v as (OCO − ) at ≈ 1647 cm −1 . 33 We used peak areas to follow the extent of reaction during HDS formation from ALD ZnO as well as HDS conversion to HKUST-1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Conformal, high-quality MOF thin-films grown on nanofibers are yet to be explored for catalytic destruction of CWAs.H erein, we show that the half-lives of the nerve agent soman (O-pinacolyl methylphosphonofluoridate,a lso known as GD) are as short as 2.3 min using our MOF-nanofiber composite catalysts.This is also the first demonstration of effective destruction of areal CWAc ompound using MOF-fabric composites,a sprevious work has only investigated simulants. [21,22] Although our previous work has shown that Al 2 O 3 and ZnO ALD can also promote MOF growth on fibers, [17,23,24] these ALD films were not used as nucleation layers in this case due to substrate incompatibility with the Al 2 O 3 ALD process and instability of ZnO in the highly acidic solvothermal solution we used. This TiO 2 ALD layer is expected to promote MOF heterogeneous nucleation on fibers, [17] and provides some contribution to catalytic CWA detoxification.…”
mentioning
confidence: 99%